Cryptococcus neoformans capsular enlargement and cellular gigantism during Galleria mellonella infection. - Rocío García-Rodas; Arturo Casadevall; Juan Luís Rodríguez-Tudela; Manuel Cuenca-Estrella; Oscar Zaragoza (PLoS ONE, 2011)
We have studied infection of Cryptococcus neoformans in the non-vertebrate host Galleria mellonella with particular interest in the morphological response of the yeast. Inoculation of C. neoformans in caterpillars induced a capsule-independent increase in haemocyte density 2 h after infection. C. neoformans manifested a significant increase in capsule size after inoculation into the caterpillar. The magnitude of capsule increase depended on the temperature, being more pronounced at 37°C than at 30°C, which correlated with an increased virulence of the fungus and reduced phagocytosis at 37°C. Capsule enlargement impaired phagocytosis by haemocytes. Incubation of the yeast in G. mellonella extracts also resulted in capsule enlargement, with the polar lipidic fraction having a prominent role in this effect. During infection, the capsule decreased in permeability. A low proportion of the cells (<5%) recovered from caterpillars measured more than 30 µm and were considered giant cells. Giant cells recovered from mice were able to kill the caterpillars in a manner similar to regular cells obtained from in vivo or grown in vitro, establishing their capacity to cause disease. Our results indicate that the morphological transitions exhibited by C. neoformans in mammals also occur in a non-vertebrate host system. The similarities in morphological transitions observed in different animal hosts and in their triggers are consistent with the hypothesis that the cell body and capsular responses represent an adaptation of environmental survival strategies to pathogenesis.